2017
DOI: 10.1080/01584197.2016.1271990
|View full text |Cite
|
Sign up to set email alerts
|

The role of avian scavengers in the breakdown of carcasses in pastoral landscapes

Abstract: Scavenging birds can provide ecosystem services to pastoralists by contributing to the breakdown of animal carcasses that can harbour and spread disease. However, these benefits have yet to be quantified in Australia. We monitored rabbit carcasses using motion-sensor cameras to identify beneficial avian scavengers across four landscape types (forest, riparian, fields with large isolated trees, and open fields) on a pastoral property in north-central Victoria. We quantified the ecosystem service of carcass brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Our study revealed that two avian scavengers, Wedgetailed Eagles and ravens, spent considerable time feeding on the carcasses of mammals shot with lead-based bullets at two areas in Victoria, and hence are likely to be at risk of ingesting lead. These results are similar to those of Peisley et al (2017), who found that raptors and corvids were the main consumers of Rabbit carcasses. However, our study was not designed to examine avian scavenging in agricultural landscapes or record reductions in carcass biomass.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study revealed that two avian scavengers, Wedgetailed Eagles and ravens, spent considerable time feeding on the carcasses of mammals shot with lead-based bullets at two areas in Victoria, and hence are likely to be at risk of ingesting lead. These results are similar to those of Peisley et al (2017), who found that raptors and corvids were the main consumers of Rabbit carcasses. However, our study was not designed to examine avian scavenging in agricultural landscapes or record reductions in carcass biomass.…”
Section: Discussionsupporting
confidence: 91%
“…First, Forsyth et al (2014) examined introduced mammalian scavengers of Sambar Deer Rusa unicolor in forested south-eastern Australia. Second, Peisley et al (2017) reported avian scavengers visiting the carcasses of non-native European Rabbits Oryctolagus cuniculus on farmland in south-eastern Australia. Finally, Rees et al (2020) assessed scavengers of kangaroos Macropus spp., feral Goats Capra aegagrus hircus and domestic Sheep Ovis aries in arid central Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot rule out that in rare cases, scavengers might disperse small pieces of infectious material in the near surroundings of a carcass in an ASF-affected region, it seems unlikely that this could have a major impact on the spread of ASF in an affected region. Previous studies suggest that scavengers may even contribute to reducing the transmission potential by removing infected material from the environment as long as they are no competent hosts for the pathogens exposed to by scavenging 66,67 . Upon ingestion, ASFV is extremely unlikely to remain infectious after passaging through the intestinal tract of a vertebrate (Sandra Blome, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…To date, research has focused on understanding the biophysical services that species provide to people (e.g., pest control, pollination) by identifying key species that act as ecosystem-service providers (Karp et al, 2013;Luck et al, 2012;Peisley et al, 2017;Whelan et al, 2008). Despite the great cultural and economic benefits associated with CES provided by species, such as wildlife viewing and aesthetic benefits, very little is known about the kinds of CES perceived by people.…”
Section: Introductionmentioning
confidence: 99%
“…Birds are globally distributed, fill various ecological roles, and provide many ecosystem services to people (Sekercioglu, 2006;Whelan et al, 2008). For example, birds provide game meat for food (Fernandes-Ferreira et al, 2011), regulate pest populations (Karp et al, 2013), act as scavengers in agricultural landscapes (Peisley et al, 2017), and disperse seeds (Pigot et al, 2016). Culturally, they drive bird-watching tourism industries (e.g., Puhakka et al, 2011;U.S.…”
Section: Introductionmentioning
confidence: 99%